El Santo vs. Mystery Science Theater 3000: Lucha Libre's Transnational Journey into American Popular Culture. - Rodriguez, Emily Rauber (Velvet Light Trap: A Critical Journal of Film & Television)
The article identifies the imperialist attitudes that characterized initial transnational encounters between North Americans and the Santo films, as well as how those framework6+s influence later depictions of lucha libre outside of Mexico. It mentions the characterization of Santo films starring masked luchador El Santo and television program 'Mystery Science Theater 3000'; and also highlights the decision of Mexican government to ban televised wrestling matches.